2021
DOI: 10.1001/jamadermatol.2021.0179
|View full text |Cite
|
Sign up to set email alerts
|

Association of Wildfire Air Pollution and Health Care Use for Atopic Dermatitis and Itch

Abstract: IMPORTANCE Air pollution is a worldwide public health issue that has been exacerbated by recent wildfires, but the relationship between wildfire-associated air pollution and inflammatory skin diseases is unknown.OBJECTIVE To assess the associations between wildfire-associated air pollution and clinic visits for atopic dermatitis (AD) or itch and prescribed medications for AD management. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional time-series study assessed the associations of air pollution resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 60 publications
0
75
1
Order By: Relevance
“…The prevalence of autism spectrum disorders (ASD) is approaching 2% in populations of all racial, ethnic and socioeconomic groups, with a fourfold male predominance ( https://www.tacanow.org/family-resources/latest-autism-statistics-2/ and https://www.cdc.gov/ncbddd/autism/data.html ). Autism is diagnosed when a patient demonstrates deficits in social interactions; a lack of social or emotional reciprocity; and learning disabilities [ 1 ]. While the diagnosis of ASD is not firmly established until 24 months of age, abnormalities in fMRI scans; preferences for geometric patterns; aberrant social communications; changes in fine motor skills; and/or characteristic eye movements can often be detected as early as 6 months of age [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of autism spectrum disorders (ASD) is approaching 2% in populations of all racial, ethnic and socioeconomic groups, with a fourfold male predominance ( https://www.tacanow.org/family-resources/latest-autism-statistics-2/ and https://www.cdc.gov/ncbddd/autism/data.html ). Autism is diagnosed when a patient demonstrates deficits in social interactions; a lack of social or emotional reciprocity; and learning disabilities [ 1 ]. While the diagnosis of ASD is not firmly established until 24 months of age, abnormalities in fMRI scans; preferences for geometric patterns; aberrant social communications; changes in fine motor skills; and/or characteristic eye movements can often be detected as early as 6 months of age [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both short‐ and long‐term exposure to wildfire smoke harm health. These health harms include exacerbation of chronic respiratory and cardiovascular conditions; increased occurrence of acute cardiovascular events and metabolic, dermatologic, and mental health disorders; increased susceptibility to respiratory infections such as influenza and SARS‐CoV‐2; immune dysfunction; adverse pregnancy outcomes; sperm damage; infant developmental disorders; and dementia 15,32‐44 . Increases in asthma attacks and asthma hospitalization are associated with wildfires.…”
Section: Effects Of Climate Change and Increased Exposure To Pollutan...mentioning
confidence: 99%
“…These health harms include exacerbation of chronic respiratory and cardiovascular conditions; increased occurrence of acute cardiovascular events and metabolic, dermatologic, and mental health disorders; increased susceptibility to respiratory infections such as influenza and SARS-CoV-2; immune dysfunction; adverse pregnancy outcomes; sperm damage; infant developmental disorders; and dementia. 15,[32][33][34][35][36][37][38][39][40][41][42][43][44] Increases in asthma attacks and asthma hospitalization are associated with wildfires. A study found that use of prescribed burns, which can decrease size and severity of wildfires, may be beneficial for immune health.…”
Section: Increasing Intensity and Frequency Of Wildfiresmentioning
confidence: 99%
“…Given the multifactorial nature of CI, it is worth exploring whether environmental factors actually contribute to its presence or intensity. Over the past decade, the associations between CI and air pollution have been explored in the context of children with AD [ 271 , 272 , 273 ]. As reported by Whang et al [ 274 ], internet search queries for the word “itch” in fact correlated with the concurrent concentration of atmospheric particulate matter <2.5 μm (PM 2.5).…”
Section: Pathogenesis Of Ckd-aimentioning
confidence: 99%